### Author Topic: Week 2 Lec 1 (Chapter 2) question  (Read 881 times)

#### Xiangmin.Z

• Newbie
• • Posts: 3
• Karma: 0 ##### Week 2 Lec 1 (Chapter 2) question
« on: January 17, 2022, 04:40:37 PM »
Hello, I have a question about example 4 from W2 L1:
We are given :$u_{t}+xu_{x}=xt$
after calculation we get:
$x=Ce^t$

$du=xt dt=Cte^t dt$, so $u=C(t-1)e^t+D=x(t-1)+D$,
but how did we get $D=\phi({xe^{-t}} )$? we know it is a constant, but why is D depended on $xe^{-t}$?

Also, why would the initial condition $u|_{t=0} =0$ implies that $\phi({x}) =x$ ?

Thanks.

« Last Edit: January 17, 2022, 07:48:04 PM by Victor Ivrii »

#### Xiangmin.Z

• Newbie
• • Posts: 3
• Karma: 0 ##### Re: Week 2 Lec 1 (Chapter 2) question
« Reply #1 on: January 17, 2022, 05:27:38 PM »
I checked the calculation and I think the answer for x is correct, and does anyone know why D is depended on $xe^{-t}$?
« Last Edit: January 17, 2022, 05:53:32 PM by Xiangmin.Z »

#### Victor Ivrii ##### Re: Week 2 Lec 1 (Chapter 2) question
« Reply #2 on: January 17, 2022, 07:48:38 PM »
Now it is correct $x=Ce^{t}$ and then $C=?$

#### Xiangmin.Z

• Newbie
• • Posts: 3
• Karma: 0 ##### Re: Week 2 Lec 1 (Chapter 2) question
« Reply #3 on: January 17, 2022, 08:19:53 PM »
$C=xe^{-t}$, so D is a function of $\phi$, therefore $D=\phi({xe^{-t}} )$ ? Yes, but "$D$  is a function of it"
« Last Edit: January 18, 2022, 04:13:44 AM by Victor Ivrii »